From Laboratory to Algorithm: The Role of Computational Methods in New Drug Design Discovery in the Digital Era - Syifa Rizkia Fajarini; Saeful Amin; Ansyirohanisa; Beni Maulana Habib; Muhammad Rahmat Darmawan (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
In the digital era, the integration of computational methods in drug discovery has revolutionized laboratory practices, enhancing efficiency and accuracy in drug development. This article provides a comprehensive review of the crucial role of computational technology in accelerating the discovery of new drug compounds, highlighting its impact on the effectiveness and success of pharmaceutical development. Traditional drug discovery methods often require extensive time and high costs, with relatively low success rates in clinical trials. To address these challenges, various computational approaches, such as Molecular Docking, Quantitative Structure-Activity Relationship (QSAR), and machine learning, have been widely adopted in the pharmaceutical industry. This study employs a systematic approach to explore different computational techniques and their applications in identifying potential drug candidates. Findings indicate that computational tools significantly expedite the drug development process, reduce costs, and improve the success rates of clinical trials. The conclusion emphasizes the importance of leveraging computational technology as an innovative strategy in pharmaceutical research and development, ultimately accelerating the discovery of safer and more effective therapies. Keywords: Computation, Drug Discovery, Digital Era, QSAR, Molecular Docking.